Growth of olive saplings in different media containing artificial and natural super absorbents at two irrigation intervals - A. Mohammadi Torkashvand; H. Shahin; M. Mohammadi (Global Journal of Environmental Science and Management)
A factorial experiment was conducted to evaluate the impact of super absorbents and organic wastes of rice, olive marc, vermicompost and farmyard manure on the soil water holding capacity and the growth of plant based on randomized complete block design with 13 treatments at two irrigation intervals 5 and 10 days. The olive saplings with same heights and better appearances were planted in an open space roofed with a plastic cover with a height of 3 m to avoid the effects of rainfall and snowfall on the results. Stockosorb superabsorbent and weighted zeolite and the rest of bulk materials were mixed. Results showed that the substrate containing 10 g/kg soil of zeolite and the substrate including 20% vermicompost +15% rice wastes +15% manure +50% soil had the best yield and can modify the effect of 10 days irrigation interval compared to the 5 days.